Volatility Spillover pada Pasar Saham Indonesia, Cina, dan India - Martin, Martin; Yunita, Yunita (Bina Nusantara University, 2010)
Globalization and advanced information technology easing us for obtaining information from global stock markets. With that condition, volatility in domestic capital market could be affected by volatility from global stock markets. The effect would have greater impact if the capital markets are located in same region. That concern will be answered in this research, about volatility spillover in Indonesia, China, and India capital market. This research using daily return data from each country indices from January 1, 2006 until April 20, 2010 applying econometric model GARCH (1,1). The result showing us that there is bidirectional volatility spillover between Indonesia and India. Meanwhile, there is only single way volatility spillover between Indonesia and China.Â